Bullous Pemphigoid Overlapping Psoriasis Vulgaris: A Rare Case Report and Literature Review - Maria-Alexandra Timofte; Constantin Căruntu; Beatrice Bălăceanu-Gurău; Irina Mărgăritescu; Călin Giurcăneanu; Mara Mădălina Mihai (Clinics and Practice)
Bullous pemphigoid (BP) is a rare autoimmune disease, primarily affecting elderly individuals, that significantly impacts the patient’s quality of life. In contrast, psoriasis vulgaris (PV) is a common, chronic, immune-mediated skin condition recognized as a systemic T-cell-mediated disorder. We aim to present the case of a patient suffering from a dermatologic association of BP and PV, which unveiled hepatitis C viral infection as a potential trigger and led to complex therapeutic challenges. A literature review is also included, exploring previous cases of overlapping BP and PV, along with a discussion of the unique pathogenic mechanisms and an analysis of the available therapeutic options. The patient, a 53-year-old male with a seven-year history of PV, presented with tense bullae overlying the psoriatic papules and plaques, with a generalized distribution. The presence of hepatitis C infection was considered a potential trigger for the concurrent presentation of BP and PV. Recent GWASs have demonstrated a potential causal relationship between PV and the subsequent development of BP, suggesting shared genetic susceptibility and immune pathways. However, the exact mechanisms driving this transition remain incompletely understood. Our case is particularly relevant as it exemplifies how environmental triggers—such as chronic hepatitis C infection—together with chronic cutaneous inflammation may act as cofactors in this process, possibly through the ‘epitope spreading’ phenomenon. This case underlines the importance of identifying triggering factors in patients with overlapping autoimmune diseases and reinforces the need for future research to further elucidate the pathogenic link between genotype and phenotype, in order to improve personalized therapeutic strategies.